2003
DOI: 10.1300/j120v37n77_10
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outcomes with Nursing Research Assignments and Citation Analysis of StudentBibliographies

Abstract: What are the library and information research requirements in a typical undergraduate nursing program? Do distance-learning library services provide undergraduate nursing students with the research materials they require for their academic work? In order to determine how the broad range of reference, instruction, and access services offered by Feinberg Library at Plattsburgh State University of New York are used by students, the author reviewed selected nursing course syllabi for research requirements and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…She compared the bibliographies of oncampus students to those completed by off-campus students. Her findings indicated that there were no significant differences in the bibliographies of these two user groups (Heller-Ross 2002). Librarians Yu, Sullivan, and Woodall compared the bibliographies of freshman-level engineering students to students in upper-level courses.…”
Section: Literature Review: Citation Studiesmentioning
confidence: 99%
“…She compared the bibliographies of oncampus students to those completed by off-campus students. Her findings indicated that there were no significant differences in the bibliographies of these two user groups (Heller-Ross 2002). Librarians Yu, Sullivan, and Woodall compared the bibliographies of freshman-level engineering students to students in upper-level courses.…”
Section: Literature Review: Citation Studiesmentioning
confidence: 99%
“…students came to the forefront as the university began preparations for the process of reaffirmation of accreditation in 2007. The library had been concerned with providing all students with equivalent library services (Chakraborty & Tuñón, 2002;Quinlan, Tuñón, & Hutchens, 2002;Ramirez & Tuñón, 2003;Tuñón, 1996Tuñón, , 1997Tuñón & Pival, 1997), using technology , 2002 to provide library training, and preparing for reaccreditation (Tuñón, 2004;). The quality of the dissertation reference lists of Ed.D.…”
Section: Questions About Quality In Edd Programs and The Research Cmentioning
confidence: 99%
“…Heller-Ross (2002) used 78 reference lists with a total of 441 citations retrieved from research papers by nursing students at Plattsburgh State University in New York to compare classes taught face-to-face with classes taught online. In a research grant at Nova Southeastern University, Tuñón, 2005a, 2005b;Tuñón & Brydges, 2005) examined 144 dissertation reference lists of students in the Child and Youth Studies Ed.D.…”
Section: Introductionmentioning
confidence: 99%
“…Like Tillotson, Lorenzen (2001), in an article about high school students' Internet research habits, used questionnaires to determine how their students located what they perceived to be quality Web resources. Heller‐Ross (2002) analyzed 78 upper‐undergraduate level nursing student research papers, which included a total of 441 citations. She determined that on‐campus students and distance students both cited relatively similar numbers of Web resources, as well as a variety of monographs and journal articles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Davis (2002) mentions that librarians are only a part of the solution, as professors need to define their expectations more clearly in regard to what is expected in the student bibliographies. Heller‐Ross (2002) notes that librarians need to work closely with departmental faculty to develop research assignments with specific guidelines. None of the research pointed to creating resource guides geared towards specific topics and courses.…”
Section: Literature Reviewmentioning
confidence: 99%